2021
DOI: 10.3389/fpls.2021.667820
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Physical and Chemical Defense Responses of Wild Emmer Wheat Against Aphids Depends on Leaf Position and Genotype

Abstract: The bird cherry-oat aphid (Rhopalosiphum padi) is one of the most destructive insect pests in wheat production. To reduce aphid damage, wheat plants have evolved various chemical and physical defense mechanisms. Although these mechanisms have been frequently reported, much less is known about their effectiveness. The tetraploid wild emmer wheat (WEW; Triticum turgidum ssp. dicoccoides), one of the progenitors of domesticated wheat, possesses untapped resources from its numerous desirable traits, including inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 91 publications
3
26
0
Order By: Relevance
“…There was no correlation between the contents of DIMBOA and its glucoside compound, DIMBOA-Glc. Similar to previous studies, DIMBOA has been found in wheat tissue when β-glucosidase activity was restricted by liquid nitrogen [9,33,34]. These results indicate that DIMBOA is synthesized constitutively in wheat leaves.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…There was no correlation between the contents of DIMBOA and its glucoside compound, DIMBOA-Glc. Similar to previous studies, DIMBOA has been found in wheat tissue when β-glucosidase activity was restricted by liquid nitrogen [9,33,34]. These results indicate that DIMBOA is synthesized constitutively in wheat leaves.…”
Section: Discussionsupporting
confidence: 89%
“…Typically, benzoxazinoids are synthesized in plastids and mobilized in the phloem sap and their effect on aphids depends on their abundance in the phloem. According to previous studies, benzoxazinoid levels in the phloem sap are much lower than that of the whole wheat leaves and aphids can avoid the higher toxicity levels of benzoxazinoids in mesophyll cells by careful probing [34,46]. Moreover, aphids can avoid the negative effects of benzoxazinoids due to the detoxification system [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…System control and data processing were performed by using the Xcalibur software (Version 4.1), Thermo Fisher, Germany). We identified the following [26,56]; ii) DIMBOA-3 Hex (2,4-dihydroxy-7methoxy-1,4-benzoxazin-3-one with three hexoses), and iii) HBOA-2 Hex (2-hydroxy-1,4benzoxazin-3-one with one hexose). Information for each BXD metabolite, including retention time, possible molecular formula, molecular weight, ion fragments in negative and positive ion modes, are presented in Supplementary Table S4.…”
Section: Benzoxazinoid Extraction Analysis and Quantificationmentioning
confidence: 99%
“…Orthologues of the maize genes BX1-BX5 and BX8-BX9, which encode the core BXD pathway, have been identified in hexaploid bread wheat (BBAADD), tetraploid wheat (BBAA), and in the three diploid progenitors of hexaploid wheat (AA, BB, and DD subgenomes; [22,23]). Although DIMBOA-Glc and HDMBOA-Glc are abundant in wheat [24][25][26], orthologous genes of BX6 and BX7 have not been fully characterized. Very recently, Sue and coworkers described the discovery and enzymatic function of four BX6 isoforms in hexaploid T. aestivum [27].…”
Section: Introductionmentioning
confidence: 99%